PENGARUH PENGETAHUAN PRODUK, RELIGIUSITAS, KUALITAS PELAYANAN TERHADAP NIAT MENGGUNAKAN PRODUK KOPERASI SYARIAH (STUDI PADA KOPERASI SIMPUL BERKAH SINERGI SYARIAH) - Anugrah, Fazel Vindo; Amalia, Alvien Nur (Journal of Accounting, Management and Islamic Economics, 2025)
This study aims to examine and determine the magnitude of the effect of product knowledge, religiosity, and service quality on the intention to use the product of the sharia synergy knot blessing cooperative product. The method used in this research is quantitative with the distribution of questionnaires followed by data analysis. The data analysis method used is multiple linear regression analysis test, f test and t test. The sample in this study were members who used the product of the sharia blessing node cooperative with a total of 100 respondents. The results of this study indicate that partially product knowledge and religiosity have no effect on the intention to use the sharia blessing knot cooperative product, and the quality of service affects the intention to use the sharia blessing node cooperative product. Simultaneously, product knowledge, religiosity, and service quality together have a significant effect on the intention to use the sharia blessing knot cooperative product. The results of the three variables tested in this study, the service quality variable that has an influence compared to product knowledge and religiosity. Therefore, the implications of this research are the management of the sharia synergy blessing node cooperative management is expected to assist its transaction activities through the application, it can make it easier for its members to withdraw funds to invest in this Sharia cooperative.